THE USER SATISFACTION LEVEL OF ELEARNING FOR BUSINESS AND MANAGEMENT SUBJECTS BASED ON TECHNOLOGY ACCEPTANCE MODEL - Indra Hastuti; Wijiyanto Wijiyanto; Wiji Lestari; Sri Sumarlinda (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
Elearning is the implementation of information technology in learning. Elearning was used in courses in Introduction to Business and Management, Business Process Management and Ebusiness. This study aims to use the Technology Acceptance model (TAM) to measure the level of user satisfaction. TAM method is used to determine the relationship between content, accuracy, format, ease of use, timelines, organizational support, user attitudes towards the information system (user attitude towards information). system) and perceived attitude of top management on the level of satisfaction of using e-learning on learning business courses and management at the Faculty of Computer Science, Duta Bangsa University Surakarta. This research is a descriptive study using the modified End User Computing Satisfaction (EUCS) approach method. The results of the evaluation study show that the 5 variables (content), the level of accuracy of the system, format, easy of use, and timeliness significantly influence user satisfaction. While organizational support variables have a significant effect on user satifaction but variable usser attitude toward information system and perceived attitude of top management has an effect but not significant to the support organization. Key words : elearning, user satisfaction, technology acceptance model, end user computing satisfaction.